50 years (and more) of German computer history. Issue 2 (3rd March 2020) - Siebert, Rainer
ABSTRACT: Those who sit in front of the computer nowadays are unlikely to be doing precisely that in front of a German computer – at least not in front of hardware with its origin in German mass production. This also applies to mobile devices which for the most part have the capability of telephoning: With a few minor exceptions, the majority of our little helpers usually come from China, Korea, Taiwan or North America. All of those who have been exposed to German computer history at one point might have observed that none of the erstwhile big names of the German computer industry or the German computer pioneers embellish today's hardware components – or do you own a Zuse notebook, a Nixdorf smartphone, let alone a tablet by Telefunken? It appears to be quite different when you consider the software market and its companies: both big names and small manufacturers exist in a vast variety of all branches and forms of company, partly ones that just entered the market and partly those who have been in business for a long time. But what exactly happened to the German manufacturers and why is current hardware labelled with the erstwhile big names associated with the German market nowhere to be found? To identify corresponding reasons and expand my knowledge about the German computer industry, I initiated a search – a search that, besides the globally experienced crisis and mistakes that have been made, also unveiled several outstanding features as well as an astonishing variety in the German market. GRAPHICAL ABSTRACT: